2010
DOI: 10.1016/j.jtbi.2010.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-stationary and ratio of expectations distributions: A comparative study

Abstract: Abstract. Many stochastic systems, including biological applications, use Markov chains in which there is a set of absorbing states. It is then needed to consider analogues of the stationary distribution of an irreducible chain. In this context, quasi-stationary distributions play a fundamental role to describe the long-term behavior of the system. The rationale for using quasi-stationary distribution is well established in the abundant existing literature. The aim of this study is to reformulate the ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
(51 reference statements)
0
19
0
Order By: Relevance
“…In recent years, there has been a rapidly growing interest in SIR-models and their applications; a comprehensive review of the existing literature and some results can be found in the survey papers by Britton [21], and Isham [34,35]. In the stochastic setting, three important quantities of the SIR-model include the final size distribution, the expected duration of an epidemic, and the basic reproduction number R 0 , which are analyzed by using a variety of tools in applied probability; see, for example, the articles by Allen [3], Allen and Burgin [4], Artalejo et al [9], and Artalejo and López-Herrero [12], among others. Gani and Purdue [27] outline a matrix-geometric method for determining the total size distribution in a recursive manner, and El Maroufy et al [25] explore how this method can be used to study SIR-models with a generalized mechanism of infection.…”
Section: (Communicated By Gail Wolkowicz)mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been a rapidly growing interest in SIR-models and their applications; a comprehensive review of the existing literature and some results can be found in the survey papers by Britton [21], and Isham [34,35]. In the stochastic setting, three important quantities of the SIR-model include the final size distribution, the expected duration of an epidemic, and the basic reproduction number R 0 , which are analyzed by using a variety of tools in applied probability; see, for example, the articles by Allen [3], Allen and Burgin [4], Artalejo et al [9], and Artalejo and López-Herrero [12], among others. Gani and Purdue [27] outline a matrix-geometric method for determining the total size distribution in a recursive manner, and El Maroufy et al [25] explore how this method can be used to study SIR-models with a generalized mechanism of infection.…”
Section: (Communicated By Gail Wolkowicz)mentioning
confidence: 99%
“…The concepts of local infectious clump and local susceptibility set are used by Ball and Neal [18] to develop a unified approach to the threshold behavior of SIR epidemics with two levels of mixing. The objective of Artalejo and López-Herrero [12] is to investigate quasi-stationarity and the ratio of expectations as two conceptually different approaches for understanding the dynamics of the SIR-model and its variant with demography before the extinction of an epidemic. New descriptors, including the time to reach specific numbers of infectives and susceptible individuals [15,Section 3.1], and the time to reach a critical number of infections [15,Section 3.2] are also investigated by using efficient numerical tools; for a related work, see the paper [5] where the interest is in the time to reach a critical number of infections in the SIR-model with infective and susceptible immigrants.…”
Section: (Communicated By Gail Wolkowicz)mentioning
confidence: 99%
“…Another possibility for the quantification of an epidemic before its extinction is the use of the so-called Ratio-of-Expectations (RE) distribution and its variants [8,11,18]. In a sense, the RE-distribution gives the 'mean' fractions of time that a population spends in the various states till the extinction of the epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…The stationary distribution of this 'returned' process that has been called also pseudo-transient distribution (see Ewens [22]) is also related to the RE-distribution. For a comparative study for the quasi-stationary and RE-distributions, we refer to the paper by Artalejo and Lopez-Herrero [8].…”
Section: Introductionmentioning
confidence: 99%
“…When the absorbing set A contains more than one state, they can be amalgamated into one single absorbing state and we can set q A = 0 and q A j = 0 for j ∈ C. Consequently, the above procedure can be applied to derive a quasi-equilibrium distribution of the Markov chain (see for example [40,13] and [121,Section 4.7]). If the state space is multi-dimensional, then we can use an appropriate bijection, as discussed in the following paragraph, which makes Q C a square matrix.…”
Section: Equilibrium and Quasi-equilibrium Behaviourmentioning
confidence: 99%